Comonomer-controlled synthesis of long-chain branched (LCB)-polyethylene. (15th August 2022) - Santoro, Orlando; Piola, Lorenzo; Mc Cabe, Karl; Lhost, Olivier; Den Dauw, Katty; Fernandez, Alvaro; Welle, Alexandre; Maron, Laurent; Carpentier, Jean-François; Kirillov, Evgueni
Graphical abstract: Highlights: α, ω-Dienes were used as long-chain branching/cross-linking agents in the ethylene polymerization catalyzed by ( n BuCp)2 ZrCl2 /MAO and rac -EBTHIZrCl2 /MAO systems. For rac -EBTHIZrCl2 -based systems, highly branched/cross-linked PEs were obtained at low diene concentrations, both in solution and in slurry conditions. Under homogeneous conditions, ( n BuCp)2 ZrCl2 -based catalysts required higher comonomer amounts to generate LCB, while linear PEs were obtained in slurry. DFT calculations were performed to rationalize the experimental results. Abstract: In this contribution, we disclose the ability of α, ω-diene comonomers, namely 1, 7-octadiene and 1–10-undecadiene, as long-chain branching (LCB)/cross-linking promoters in the ethylene polymerization catalyzed by bis(indenyl) and bis(cyclopentadienyl) catalyst systems, namely rac -EBTHIZrCl2 (Zr -1) and ( n BuCp)2 ZrCl2 (Zr-2 ). Both under homogeneous and heterogeneous (slurry) conditions, Zr-1 -based systems efficiently produced LCB/cross-linked polymers even with very small amounts of diene, as demonstrated by melt rheology measurements. On the other hand, higher co-monomer concentrations were required for the homogeneous Zr-2 /MAO system, while only linear PEs were isolated in the presence of its silica-supported version supp -Zr-2 operated under heterogeneous conditions, regardless of the amount of diene employed. Rheological and NMR spectroscopy studies proved that consumption of the diene and formation of LCB/cross-linked structures take place during the early stages of the polymerization. The experimental observations were rationalized by DFT computations.